Heterosis in bacterial wilt resistant tomato - Rani PR (Department of Olericulture, College of Horticulture, 2000)
The investigation on "Heterosis in bacterial wilt resistant tomato" was undertaken in the Department of Olericulture, College of Horticulture, Vellanikkara during the period from June, 1999 to March 2000. The findings are mentioned below. Five bacterial wilt resistant genotypes viz., LE 415, Sakthi, Mukthi, LE 421 and BWR-l were crossed in a diallel fashion (without reciprocals) to produce ten F 1 hybrids. These F 1 hybrids along with the parents were evaluated for resistance to bacterial wilt in a wilt sick plot. The F 1 hybrids LE 415 x Mukthi, LE 415 x Sakthi, LE 415 x BWR-l and Sakthi x Mukthi were found to be resistant. The general combining ability of the parents and the specific combining ability of the crosses were estimated. The good general combiner for fruits/plant was LE 415 x Mukthi (48.2 fruits/plant). This hybrid was the best general combiner for fruit yield/plant (1.5 kg/plant). The relative heterosis, standard heterosis and heterobeltiosis for . different biometric characters were estimated. LE 415 x Mukthi was the best F 1 hybrid for fruits/plant (48.2 fruits/plant), fruit yield/plant (l.5 kg/plant) and average fruit weight (43.15 g). This hybrid was resistant to both radial and concentric fruit cracking. It was also tolerant to mosaic disease and tomato spotted wilt virus.